From a reward to a social right: experiences and points of view of Gypsy beneficiaries of the Social Integration Revenue Policy - Ayala Rubio, Ariadna (Revista de Antropología Social, 2013)
This article presents the different points of view of gypsy beneficiaries of the Social Integration Revenue Policy of the Region of Madrid, Spain. The discourses of the people interviewed are presented in relation to their relative social standing and the socio-economic features that are most relevant in explaining their narratives. Special emphasis is placed on describing the way in which they present themselves in order to obtain this social income, and on analysing the elements they make reference to in arguing their legitimacy as recipients. Through the description of some paradigmatic experiences, the different strategies employed in their relations with social workers are introduced.